Surface Roughening with Iron Nanoparticles for Promoted Adhesion of Spin Coated Microsupercapacitor Electrodes. (14th January 2019) - Vyas, A.; Li, Q.; Cornaglia, F.; Wang, K.; Anderson, A.; Haque, M.; Kuzmenko, V.; Smith, A. D.; Lundgren, P.; Enoksson, P.
Abstract: Microsupercapacitors (MSCs) are miniaturized energy storage devices that can be integrated in an on-chip platform as a component of a power supply for Internet of things' sensors. Integration of these on-chip MSCs require them to be fabricated through CMOS compatible fabrication techniques such as spin coating. One of the biggest challenges in spin coated MSCs is the poor surface adhesion. In this work, we present a CMOS compatible electrode deposition process with enhanced adhesion and retention for reduced graphene oxide (rGO) using spin coating. In order to improve the adhesion and surface uniformity of the deposited electrode material, the surface of Si/SiO2 wafers was subjected to roughening through Fe nanoparticle formation. A 4 nm thick Fe layer deposition substantially magnified the average mean surface roughness of the substrates. In comparison with substrates without the Fe deposition, the treated ones have more than 300% improvement in surface coverage and rGO mass retention after sonication testing. These results suggest that the surface roughening has a positive influence on electrode deposition via a spin-coating method.